Correction: Impedimetric measurement of DNA–DNA hybridisation using microelectrodes with different radii for detection of methicillin resistant Staphylococcus aureus (MRSA). Issue 15 (5th July 2017) - Li, Poh Quan; Piper, Andrew; Schmueser, Ilka; Mount, Andrew R.; Corrigan, Damion K.
Abstract : Correction for 'Impedimetric measurement of DNA–DNA hybridisation using microelectrodes with different radii for detection of methicillin resistant Staphylococcus aureus (MRSA)' by Poh Quan Li et al., Analyst, 2017, 142, 1946–1952.